Comparison of National Well-being of Mediterranean Countries in terms of EU: Turkey, Italy, Spain - Ince, Fatma (Acta Scientiarum. Health Sciences, 2024)
Global developments are leading change by finding answers in various ways for different nations. In addition to technological, economic, and financial developments, psychological and sociological developments also draw attention. While extraordinary situations such as a pandemic, global crises, and famine accelerate change, they inevitably shorten the adaptation process. Considering all developments in terms of different cultures enables us to benefit from the advantages of comparative studies. From this point of view, in this study, the issue of national welfare is discussed in terms of three Mediterranean countries and compared with the EU. In the study, in which the concept of well-being, which is discussed in seven dimensions, is supported by economic indicators, there are statistical differences between countries.